2020
DOI: 10.1002/tox.23081
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 ameliorates reproductive function injury in C57BL/6J mice induced by di‐N‐butyl‐phthalate

Abstract: With the aggravation of environmental pollution, the incidence of infertility is increasing. Ginsenoside Rg1 is a monomer component extracted from Panax ginseng. It has been found that Ginsenoside Rg1 is able to prevent premature ovarian failure and delay testicular senescence. Therefore, we speculate Ginsenoside Rg1 may have great potential to prevent and treat infertility. The aim of this work is to explore whether Ginsenoside Rg1 plays a protective role in the dinbutyl phthalate (DBP)‐induced reproductive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…Emerging reports have validated the efficacy of Chinese medicine herbs in S-AKI, such as honokiol [31], resveratrol [32], and shionone [33]. Rg1 is the main active component of Panax ginseng and has many pharmacological properties [34]. In recent years, the protection afforded by Rg1 has been confirmed in sepsis [35] and sepsis-related diseases, including septic acute lung injury [36], septic cardiac dysfunction [37], and septic encephalopathy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging reports have validated the efficacy of Chinese medicine herbs in S-AKI, such as honokiol [31], resveratrol [32], and shionone [33]. Rg1 is the main active component of Panax ginseng and has many pharmacological properties [34]. In recent years, the protection afforded by Rg1 has been confirmed in sepsis [35] and sepsis-related diseases, including septic acute lung injury [36], septic cardiac dysfunction [37], and septic encephalopathy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosid Rg1 đã cải thiện số lượng và khả năng di chuyển của tinh trùng, giảm tổn thương mô tinh hoàn, tăng nồng độ testosterone và hormone tạo hoàng thể trong huyết thanh, đồng thời giảm nồng độ hormone kích thích nang trứng trong huyết thanh ở chuột nhắt bị tổn thương chức năng sinh sản gây ra bởi dinbutyl phthalat. Cơ chế là do ginsenosid Rg1 điều hoà biểu hiện mức protein liên quan đến quá trình sinh tinh, Cx43, E-cadherin, p-PI3K (phosphatidylinositol 3kinase), p-Akt và mTOR (mammalian target of rapamycin) ở chuột được quan sát bằng cách sử dụng xét nghiệm hóa mô miễn dịch, xét nghiệm PCR (polymerase chain reaction) định lượng thời gian thực và phân tích Western blot [76]. Ngoài ra, tác dụng cải thiện mào tinh hoàn, tinh hoàn, số lượng và khả năng di chuyển của tinh trùng và nồng độ testosteron huyết thanh của ginsenosid Rg1 cũng đã được báo cáo trên đối tượng chuột cống bị vô sinh gây ra bởi ethanol [77].…”
Section: Một Số Nghiên Cứu đáNh Giá Tác Dụng đIều Hoà Hormon Steroid ...unclassified
“…Furthermore, it demonstrated the potential to enhance the reproductive function of aging mice affected by D-galactose-induced impairment by up-regulating the expression of granulocyte follicle-stimulating hormone receptor and down-regulating the aging signaling pathways P53-P21-P19/stk, P16, and Bax/Bcl-2 [ 22 ]. Dai et al showed that long-term administration of ginsenoside Rg1 could improve the fertility of naturally aging mice, which might be related to the obvious antioxidant effect on the ovary [ 23 , 24 ]. The antiovarian aging activities of Rg1 have received extensive attention, but it inhibited age-induced GSCs loss has not been clarified.…”
Section: Introductionmentioning
confidence: 99%